Entre estetoscópios e corações: o encontro da ciência e da sensibilidade ao longo da minha jornada acadêmica - Silva, Renata Postel (Universidade Federal de São Carlos, 2024)
This paper, presented as part of the medicine graduation course at the Federal University of São Carlos (UFSCar), focuses on a reflective narrative of the experiences, challenges, and lessons learned throughout the student's academic journey. The narrative also emphasizes the significant role of extracurricular activities in the student's personal and professional development, broadening her perspective and providing a more comprehensive view of medicine. Throughout her undergraduate studies, the student had the opportunity to engage in practical experiences across various healthcare environments, participating in extension programs and internships that exposed her to diverse realities within the healthcare system. These experiences contributed to the enhancement of both clinical skills and the ability to manage complex situations. Particularly, the extension activities offered by UFSCar, known as ACIEPEs, were instrumental in strengthening her commitment to ethics, empathy, holistic care, active listening and humanized patient care – key aspects in shaping a medical professional capable of addressing the contemporary challenges of the medical profession.
Between stethoscopes and hearts: the meeting of science and sensitivity throughout my academic journey
Keywords: Educação médica; Atividades extracurriculares; ACIEPE; Formação profissional; Humanização; CIENCIAS DA SAUDE::MEDICINA